Time-reversal anomalies of QCD3 and QED3 - Po-Shen Hsin (Journal of High Energy Physics)
Abstract Anomalies of global symmetry provide powerful tool to constrain the dynamics of quantum systems, such as anomaly matching in the renormalization group flow and obstruction to symmetric mass generation. In this note we compute the anomalies in 2+1d time-reversal symmetric gauge theories with massless fermions in the fundamental and rank-two tensor representations, where the gauge groups are SU(N), SO(N), Sp(N), U(1). The fermion parity is part of the gauge group and the theories are bosonic. The time-reversal symmetry satisfies T 2 = 1 or T 2 = M $$ \mathcal{M} $$ where M $$ \mathcal{M} $$ is an internal magnetic symmetry. We show that some of the bosonic gauge theories have time-reversal anomaly with c − ≠ 0 mod 8 that is absent in fermionic systems. The anomalies of the gauge theories can be nontrivial even when the number of Majorana fermions is a multiple of 16 and ν = 0.